Technological Infrastructure as a Strategy for Profitability in a Construction Company, Peruvian Case - Giron, Smith Osmar Cubas; Gastelo, Melva Yaseni Diaz; Rodriguez, Victor Hugo Puican (Journal of Ecohumanism, 2024)
The objective of the study was to determine the relationship between technological infrastructure and profitability in a construction company in Chiclayo, 2024, the methodology was based on an applied study, quantitative approach, non-experimental design, longitudinal and correlational scope, included 12 financial statements for the years 2018 to 2023 and 32 workers; the technique was documentary review of financial statements and the instrument with the data collection form and the survey with two questionnaires, the results showed a regular level of technological infrastructure (53.1%), the economic profitability went from 0.68 in 2018 to 7.22 in 2023, while the financial profitability from 4.59 to 7.22 and the sales profitability went from 1.87 to 13.19; The direct significant relationship between technological infrastructure and profitability in a construction company in Chiclayo was demonstrated; that is, the more the company focuses on improving its investment in the acquisition of technological tools, the greater the profitability of the organization; on the contrary, when the company does not give sufficient importance to improving technology, the company’s profitability also decreases.